PENGARUH PENJUALAN PERSONAL TERHADAP PENGETAHUAN PRODUK DAN IMPLIKASINYA TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUV PREMIUM DI JAWA BARAT - Wardhana, Aditya; Iba, Zainuddin (JURNAL KEBANGSAAN, 2014)
This research can provide useful information about the importance of personal selling in building customer knowledge against the products offered by the company (product knowledge), which in turn implies an increase in consumer purchasing decisions. Research using multistage area sampling which combined between cluster random sampling and systematic random sampling done on the consumers car dealer shops in the city of Bandung, as many as 400 respondents as samples. This research using survey method with the quantitative approach. While this research type is descriptive research and verificative explanatory research. To test the hypothesis of research statistical methods used path analysis. Test results found a significant relationship between sales personnel with knowledge of the product, other than that of the test results found no significant influence between the personal selling and product knowledge of the consumer buying decisions either partially or simultaneous.Keywords: Personal Selling, Product Knowledge, Consumer Buying Decision